Molecular Mechanisms and Emerging Therapeutic Targets of Triple-Negative Breast Cancer Metastasis - Neophytou, Christiana; Boutsikos, Panagiotis; Papageorgis, Panagiotis (Frontiers in Oncology, 2018)
Breast cancer represents a highly heterogeneous disease comprised by several subtypes with distinct histological features, underlying molecular etiology and clinical behaviors. It is widely accepted that triple-negative breast cancer (TNBC) is one of the most aggressive subtypes, often associated with poor patient outcome due to the development of metastases in secondary organs, such as the lungs, brain and bone. The molecular complexity of the metastatic process in combination with the lack of effective targeted therapies for triple-negative breast cancer metastasis have fostered significant research efforts during the past few years to identify molecular “drivers” of this lethal cascade. In this review, the most current and important findings on triple-negative breast cancer metastasis, as well as its closely associated basal-like subtype, including metastasis-promoting or suppressor genes and aberrantly regulated signaling pathways at specific stages of the metastatic cascade are being discussed. Finally, the most promising therapeutic approaches and novel strategies emerging from these molecular targets that could potentially be clinically applied in the near future are being highlighted.